Bilateral Crush Injury of the Proximal Tibial Physis in an Adolescent Gymnast: A Case Report. Issue 2 (April 2015) - Balazs, George C.; Polfer, Elizabeth M.; Jex, Jefferson W.
Abstract : Case: A thirteen-year-old female gymnast experienced bilateral knee pain after landing from a jump off a vault during a competition. Initial radiographs revealed negative findings, but magnetic resonance imaging demonstrated periphyseal osseous edema of the proximal parts of the tibiae. The patient later developed an anterior physeal bar on the right side, with recurvatum deformity. Conclusion: Despite similar initial imaging findings bilaterally and identical mechanisms of injury, only the injury on the right side met the strict criteria for classification as a Salter-Harris type-V injury. This case illustrates the difficulty encountered with current diagnostic criteria for type-V injuries.